Окреслення перспектив використання декоративних багаторічників спонтанної флори урочища Феофанія - Matiashuk, Raisa; Gubar, Liubov; Pirko, Inna (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2021)
The taxonomic and ecological structure of an artificial set of species of spontaneous flora of the local landscape Feofaniya, distinguished by decorative features, is presented. Decorative perennials, with the exception of aquatic and coastal ones, number 147 species. They are considered taking into account the adaptive characteristics, as a potentially basic component of the regional assortment of ornamental plants for landscaping. In terms of taxonomic composition, the species belong to 100 genera from 38 families. A significant part of perennials is rare in ornamental gardening. Among the studied perennials, the rare fraction includes 13 species with international (four species), state (seven species), or regional (six species) conservation status. According to the results of bioecological analysis, the predominance of mesophytic (76 %), heliophytic (44 %), mesotrophic (82 %), and neutrophilic (65 %) species is shown. When considering the ecological affiliation, the studied species are united into 15 principal ecomorphological groups. The use of plants represented in such groups as the main assortment in the landscaping of the corresponding ecotopes is a prerequisite for the stability and durability of such artificial communities as flower arrangements. The proposed assortment ensures the creation of modern low-cost flower arrangements, as well as the preservation of the biodiversity of the local flora by expanding the cultigen range of these species.